Significance of Transrectal Ultrasonography in Infertile Patients with Persistently Elevated Bacteriospermia (Journal of Fatima Jinnah Medical University, 2018)
Objective: To establish the significance of transrectal ultrasound to identify and define prostate and seminal vesicle abnormalities in patients with chronic male accessory gland infection (MAGI) who failed to respond to antibacterial treatment. Methods: We selected 50 consecutive patients with MAGI and persistently elevated bacteriospermia (≥ 106 colony forming units [CFU]/mL) after three antibiotic courses. All patients underwent transrectal ultrasonography (TRUS) scans and semen analysis. Results: TRUS revealed hyperechogenicity with areas of calcifications in 90% (n=45) of patients with MAGI. Conclusion: Although antibiotic therapy is considered suitable when microbial MAGI is suspected, it is impossible to account for a poor response to antibiotics merely on the basis of conventional criteria (clinical history, physical and ejaculate signs). Thus, TRUS may be helpful in the follow-up of these patients
Keywords: : persistent bacteriospermia; male infertility, chronic prostatitis, transrectal ultrasound